2005
DOI: 10.1093/annonc/mdi242
|View full text |Cite
|
Sign up to set email alerts
|

Metachronous gastric MALT lymphoma and early gastric cancer: is residual lymphoma a risk factor for the development of gastric carcinoma?

Abstract: Prolonged residual GML could constitute an additional risk factor for the development of gastric carcinoma. Long-term endoscopic surveillance is mandatory in patients treated conservatively for gastric MALT lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 19 publications
3
37
0
2
Order By: Relevance
“…Longer follow-up is needed, however, to determine its long-term efficacy and to quantify the risk for late side effects. Although the risk for second malignancies is low [84], this cannot be neglected, especially in patients who may already have an increased incidence of gastric cancer, because of the link between H. pylori infection and the development of gastric adenocarcinoma [85,86]. Remission with chemotherapy has been described in a patient who relapsed following partial gastrectomy and postoperative radiation [87].…”
Section: Thementioning
confidence: 99%
“…Longer follow-up is needed, however, to determine its long-term efficacy and to quantify the risk for late side effects. Although the risk for second malignancies is low [84], this cannot be neglected, especially in patients who may already have an increased incidence of gastric cancer, because of the link between H. pylori infection and the development of gastric adenocarcinoma [85,86]. Remission with chemotherapy has been described in a patient who relapsed following partial gastrectomy and postoperative radiation [87].…”
Section: Thementioning
confidence: 99%
“…This risk is increased by combination therapy including chemotherapy and radiation therapy [1,3,8]. Chemotherapy is not known to induce solid tumors, but can potentiate the effect of other treatments [8,14]. In a study of about 139 patients treated for gastric lymphoma, the authors found that CHOP type chemotherapy is associated with a higher risk of second gastric cancer (p=0.009) [13].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of about 139 patients treated for gastric lymphoma, the authors found that CHOP type chemotherapy is associated with a higher risk of second gastric cancer (p=0.009) [13]. Further, it is possible that alkylating agents exert a mutagenic and carcinogenic effect [1,3,7,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Les patients atteints d'un LGM sont à risque de dé velopper un second cancer [18] mais é galement et surtout un cancer gastrique. Celui-ci peut ê tre synchrone [18] ou mé tachrone [7]. La surveillance endoscopique doit permettre de le dé pister au stade pré coce et espé rer une gué rison complè te au prix d'une gastrectomie totale.…”
Section: Traitements é Radication De H Pyloriunclassified